Superconductivity in Pt- and La-Doped BaFe2As2 Compounds Prepared by Solid-State Reaction - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
We report magnetization, resistivity, and heat capacity measurements on samples of BaFe2As2, BaFe1.9Pt0.1As2, and Ba0.7La0.3Fe1.9Pt0.1As2 that have been prepared by solid-state reaction. Standard four-probe transport measurements in the temperature range 4.2-300 K showed that the substitution of non-isoelectronic Pt for Fe produced an electron-doped situation resulting in a superconductive phase transition at T-c = 24 K. Furthermore, we observe that the coupled spin-density-wave/antiferromagnetic transition which occurs for the BaFe2As2 sample at 140 K, as expected, also occurs in the Pt-doped BaFe1.9Pt0.1As2 sample with only a small decrease in critical temperature to 138 K. We have also investigated in detail the superconducting state with magnetization measurements in the temperature range 5-400 K, up to a field of 9 T. From the magnetization data for BaFe1.9Pt0.1As2, we observe that T-c = 21.7 K, which is in good agreement with the resistivity measurement. The zero-field cooled results correspond to a large Meissner fraction. In Ba0.7La0.3Fe1.9Pt0.1As2, we also see a large diamagnetic response, with a reduction in T-c to 19.6 K. In addition, we analyzed heat capacity measurements for the electronic and phonon behavior of these materials. The analysis shows an excess entropy associated with the change in electronic behavior that is consistent with what is expected for Fe local moments, pointing to an electronic density of states that is based on a spin-fluctuation mechanism. We discuss the results in relation to a varying electronic density of states present in the samples and a possible pseudogap induced by addition of Pt.
Keywords: DC magnetic susceptibility; Meissner effect; spin density wave (SDW); superconductivity